2020
DOI: 10.3390/biom10050768
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Effects of Peritoneal Dialysis Solutions on the Peritoneal Membrane: The Role of Oxidative Stress

Abstract: One of the main limitations to successful long-term use of peritoneal dialysis (PD) as a renal replacement therapy is the harmful effects of PD solutions to the structure and function of the peritoneal membrane (PM). In PD, the PM serves as a semipermeable membrane that, due to exposure to PD solutions, undergoes structural alterations, including peritoneal fibrosis, vasculopathy, and neoangiogenesis. In recent decades, oxidative stress (OS) has emerged as a novel risk factor for mortality and cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 86 publications
1
48
0
6
Order By: Relevance
“…These findings confirm ROS, and specifically mtROS, as key mediators in the process of PD-mediated EMT. These results are consistent with in vitro studies in other cell types, and also in mesothelial cells, showing that TGF-β1 also increases the generation of mtROS, resulting in inflammatory response, phenotype transition and, finally, fibrosis [ 19 , 20 , 29 , 33 ]. On the other hand, we also observed a significant decrease of mitochondrial membrane potential in cells affected by EMT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings confirm ROS, and specifically mtROS, as key mediators in the process of PD-mediated EMT. These results are consistent with in vitro studies in other cell types, and also in mesothelial cells, showing that TGF-β1 also increases the generation of mtROS, resulting in inflammatory response, phenotype transition and, finally, fibrosis [ 19 , 20 , 29 , 33 ]. On the other hand, we also observed a significant decrease of mitochondrial membrane potential in cells affected by EMT.…”
Section: Discussionsupporting
confidence: 89%
“…There is a clear connection between mitochondrial damage, oxidative stress and inflammation [ 21 , 28 ], as well as between chronic inflammation and fibrosis, including peritoneal fibrosis [ 10 , 29 ]. According to this point of view, inflammation could antedate membrane fibrosis, and even the relationship between these two processes could be bidirectional, each one inducing the other [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…They accumulate with rising age and contributing factors such as hyperglycemia, hyperlipidemia, oxidative stress and other illnesses which affect the renal system [ 60 , 61 ]. Several studies pointed to a strong association between oxidative stress and the level of AGEs [ 20 , 21 , 22 ]. Moreover, with AGEs’ association with inflammation, oxidative stress and uremic state due to CKD, it could be hypothesized that all of these factors cumulatively contribute to cardiovascular mortality and morbidity in CKD/HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the heat sterilization process of the PD fluids, glucose degradation products are accumulated in the peritoneum and they trigger the formation of AGEs in excessive amounts, leading to an increased oxidative stress [ 20 ]. During HD, it was shown that the reactive carbonyl compounds accumulated due to renal failure and the interaction of blood with the dialysis membrane, both contributing to an amplified formation of AGEs [ 15 , 21 ]. Consequential formation of oxidative products, loss of important antioxidants and chronic inflammation are the most significant factors that lead to high cardiovascular risk and increased mortality in CKD/HD settings [ 11 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The peritoneum is composed of a monolayer of mesothelial cells, supported by connective tissue, underneath of which there are blood vessels, nerves, and lymphatic vessels. In long-term PD, the PM serves as a semipermeable barrier for ultrafiltration, and diffusion may present structural alterations, including peritoneal fibrosis (PF), vasculopathy, and angiogenesis, which are leading causes of peritoneal ultrafiltration failure (Roumeliotis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%